Three Novel Players: PTK2B, SYK, and TNFRSF21 Were Identified to Be Involved in the Regulation of Bovine Mastitis Susceptibility via GWAS and Post-transcriptional Analysis - Yang, Fan; Chen, Fanghui; Li, Lili; Yan, Li; Badri, Tarig; Lv, Chenglong; Yu, Daolun; Zhang, Manling; Jang, Xiaojun; Li, Jie; Yuan, Lu; Wang, Genlin; et al. (Frontiers in Immunology, 2019)
Bovine mastitis is a common inflammatory disease caused by multiple factors in early lactation or dry period. Genome wide association studies (GWAS) can provide a convenient and effective strategy for understanding the biological basis of mastitis and better prevention. 2b-RADseq is a high-throughput sequencing technique that offers a powerful method for genome-wide genetic marker development and genotyping. In this study, single nucleotide polymorphisms (SNPs) of the immune-regulated gene correlative with mastitis were screened and identified by two stage association analysis via GWAS-2b-RADseq in Chinese Holstein cows. We have screened 10,058 high quality SNPs from 7,957,920 tags and calculated their allele frequencies. Twenty-seven significant SNPs were co-labeled in two GWAS analysis models (Bayesian (P<0.001) and Logistic regression (P<0.01)), and only three SNPs (rs75762330, C>T, PIC=0.2999; rs88640083, A>G, PIC=0.1676; rs20438858, G>A, PIC=0.3366) were annotated to immune-regulated genes (PTK2B, SYK and TNFRSF21). Identified three SNPs are located in non-coding regions with low or moderate genetic polymorphisms. However, independent sample population validation (Case-control study) data showed that three important SNPs (rs75762330, P<0.025, OR>1; rs88640083, P<0.005, OR>1; rs20438858, P<0.001, OR<1) were significantly associated with clinical mastitis trait. Importantly, PTK2B and SYK expression was down-regulated in both peripheral blood leukocytes of clinical mastitis cows and in vitro LPS (E. coli)–stimulated bovine mammary epithelial cells, while TNFRSF21 was up-regulated. Under the same conditions, expression of Toll-like receptor 4 (TLR4), AKT1 and pro-inflammatory factors (IL-1β and IL-8) were also up-regulated. Interestingly, network analysis indicated that PTK2B and SYK are co-expressed in innate immune signaling pathway of Chinese Holstein. Taken together, these results provided strong evidence for the study of SNPs in bovine mastitis, and revealed the role of SYK, PTK2B and TNFRSF21 in bovine mastitis susceptibility/tolerance.